Dampak E-Commerce dan Digitalisasi Perpajakan Terhadap Kinerja UMKM yang Dimoderasi Insentif Pajak - Etanim, Frialdo (Universitas 17 Agustus 1945 Jakarta, 2022)
This study has a goal, namely (1) to determine the effect of using E-commerce on the performance of UMKM during the covid 19 period in West Jakarta (2) To determine the effect of digitalization of taxation on the performance of UMKM during the Covid 19 period in West Jakarta (3) To determine the effect of incentives taxes during covid 19 on the performance of UMKM during the covid-19 period in West Jakarta, (4) to find out the use of E-commerce on the performance of UMKM in West Jakarta with taxpayer incentives during covid 19 as a moderating variable, and (5) to determine the effect of digitalization taxation on the performance of UMKM in West Jakarta with tax incentives during covid 19 as a moderating variable. . To determine the number of sample respondents using purposive sampling technique, the sample obtained is 100 respondents from SMEs. This study analyzes the relationship between the influence of e-commerce utilization and tax digitalization on MSME performance with tax incentives during covid-19 with the data analysis technique used in this study is Structural Equation Modeling (SEM) with PLS (Partial Least Square) software. The results of the analysis obtained in this study that the use of e-commerce has a positive and insignificant effect on the performance of MSMEs, digitization of taxation has a positive and significant effect on the performance of MSMEs, tax incentives have a positive and significant effect on the performance of MSMEs, the use of e-commerce has a positive and significant effect on the performance of MSMEs. through tax incentives during covid-19 and digitization of taxation has a positive and significant impact on the performance of MSMEs through tax incentives during covid-19